Models of finite elements in solution of temperature fields’ problems - Turskienė, Sigita (Lietuvos matematikos rinkinys, 1997)
The paper deals with ways of modelling the junction zones of thin walled branched structures by finite elements in solving temperature fields’ problems. An adjoint spatial finite element with a rectangular basis is suggested for discretization. Coordinate transformation and temperature phenomena re-calculation formulas have been obtained. They allow to build a grid of finite elements of the investigated object by using angular as well as middle of the sides of a prism points. The numerical examples are presented. Present solutions are compared with available control solutions.